Food Intake During Cancer Therapy: A Systematic Review. (November 2020) - Conigliaro, Teresa; Boyce, Lindsay M.; Lopez, Carlos A.; Tonorezos, Emily S.
Abstract : Aim: Conduct a systematic review of available evidence on food and beverage intake during cancer treatment. Objective: Determine what food or beverages consumed during cancer treatment might prevent recurrence, subsequent malignancies, treatment-related toxicity, or death. Background: Food and beverage intake, as well as weight status, can integrate with cancer treatment to mitigate treatment-related toxicities, support treatment success, and prevent recurrence. Yet, evidence-based recommendations are lacking. Methods: We searched PubMed, Embase, and Cochran for research studies conducted within the last 10 years on food and beverage consumption during cancer treatment, with no restrictions on age or cancer type. Two reviewers independently extracted information on intervention type, diet, and outcomes; these data were confirmed by a third reviewer. Results: Nineteen studies were selected from 1551 potential studies. Nine were randomized controlled trials, analyzing high protein diets, short-term fasting, low-fat diets, FODMAP diet, or comparing consumption of 1 specific food or nutrient, including Concord grape juice, onions, and fiber. The remaining 10 studies were observational or retrospective and tracked treatment symptoms, general dietary intake, or weight status as well as consumption of specific foods including nuts, coffee, sugar-sweetened beverages. Conclusions: Available evidence suggests food can be effective at ameliorating cancer treatment-related toxicities and improving prognosis, but more research is needed. Abstract : Supplemental Digital Content is available in the text.